Scientific Prototypes as Analogies of Nature - Rothbart, Daniel (Theoria et Historia Scientiarum, 2008)
In this paper I explore how certain Kuhnian themes concerning the evolution of science are given a more nuanced reading through a study of scientific analogy. I argue that many scientific discoveries are inspired by analogical models (Section 1), that such models often function as prototypes (not paradigms) for developing a particular target system (Section 2), and that prototype modeling is particularly valuable for designing modern scientific instruments (Section 3). From this discussion of scientific analogy, we discover that the endorsement of prototype models often precipitates severe strains in the literal vocabulary at a particular